SAVAGE: Simulation of Virtual Reality-Based for Building Fire Victim Rescue Learning Media - Nugraha, Wildan; Supri, Supri; Abdullah, Anton; Komalasari, Yeti (Graduate Program Magister Manajemen Pendidikan, 2024)
Airports are very dynamic and complex environments, making them high-risk places for incidents and accidents, both due to the aircraft's movement and to the building facilities or structures at the airport. Emergency service personnel must have high skills in emergency response, quick decision-making abilities, and a deep understanding of the various dangerous situations that may be encountered in the field. Continuous education and training are essential to ensure their readiness and ability to deal with emergencies. This study aims to develop Virtual Reality-based Search and Rescue learning media to improve the skills and understanding of training participants in search and rescue operations. This learning media is designed to provide a realistic and interactive simulation experience, allowing participants to practice rescue procedures in various dangerous scenarios without real risk. The development methods used in this study include the stages of needs analysis, design, development, implementation, and evaluation (ADDIE). At the analysis stage, the identification of training needs and competencies that must be achieved is carried out. The design stage involves designing Virtual Reality scenarios that cover various field conditions and rescue techniques. Effectiveness is evaluated by measuring the increase in skills and understanding of participants before and after using Virtual Reality media. The study results indicate that this learning media effectively improves the operational and decision-making skills of training participants in emergency situations. The feasibility assessment by media experts obtained an average score of 88.72%. Then, the feasibility assessment by material experts obtained an average score of 88.90%. After conducting a product trial on students, the evaluation results were 81.30%. Based on the results of the validation and trial of this product, Virtual Reality-based learning media can be recommended as an innovative and efficient training tool for Search and Rescue learning media.